Pushing the Limits of Cancer Therapy: The Nutrient Game - Lettieri-Barbato, Daniele; Aquilano, Katia (Frontiers in Oncology, 2018)
The standard cancer treatments include chemotherapy, radiotherapy or their combination, which are generally associated with a multitude of side effects ranging from discomfort to the development of secondary tumours and severe toxicity to multiple systems including immune system. Mounting evidence has highlighted that the fine-tuning of nutrients may selectively sensitize cancer cells to conventional cancer therapies, while simultaneously protecting normal cells from their side effects. Nutrient modulation through diet also improves cancer immunesurveillance in a way that severe immunosuppression could be avoided or even the immune response or immune-based cancer therapies be potentiated also through patient microbiota remodelling. Here we review recent advances in cancer therapy focusing on the effects of adjuvant dietary interventions (e.g. ketogenic diets, fasting) on the metabolic pathways within cancer cells and tumour environment (e.g. microbiota, immune system, tumour microenvironment) that are involved in cancer progression and resistance as well as cancer cell death. Finally, based on the overall literature data, we designed a nutritional intervention consisting in a plant-based moderate ketogenic diet that could be exploited for future pre-clinical research in cancer therapy.